Role of change leadership in attaining sustainable growth and curbing poverty: A case of Pakistan tourism industry - Bashir, Fatima; Tahir, Zara; Aslam, Amna (Frontiers in Psychology, 2022)
The current study has proposed to apply change leadership as a vehicle forward for sustaining growth of tourism industry to eradicate poverty through Pakistani tourism industry. Applying a mixed method approach the current paper has attempted to uncover the role a change leader can play to help achieve the United Nations sustainable development goals of poverty reduction. In initial phase termed as study one the authors interviewed stake holders of tourism industry to find out the major drivers of the industry and identify the leadership style that may prove to be effective in said industry. In the next phase of the study, a survey method approach was used where different tourism companies and hotel chains were included for analysis. The aim of study two was to check employees’ perception of change leadership and its impact on their resilience and ultimately the sustainable organization performance of companies’ operationalizing in the sector with moderating impact of sustainable tourism attitude in times of a crisis. 430 Full-time workers in the tourism industry were contacted for a self-administered survey achieving a response rate of 83%. The findings of the study confirmed that in presence of a change leader the process of adaptation to sudden changing situations amidst financial crises, pandemic and climatic change, becomes bearable and employees are able to cope with the work situations without pushing them to quit the industry. The study has a significant contribution toward a rapidly growing and focused industry which can play a major role in the economy of any country leading to job creation and poverty reduction. The study further opens avenues for researchers to investigate boosters for the industry as tourism plays an important role not just in growing economies but also in healthy lifestyles contributing to the mental health of individuals.